Differential cellular increase in cerebrospinal fluid after encephalography in mentally retarded patients - Iivanainen, M. (1974)
The behaviour of the CSF cells during gas encephalography (GEG) with O(2), N(2)O, and halothane is poorly known in cerebral developmental disorders. One hundred and fifty CSF samples taken during pneumoencephalography from 75 mentally retarded patients were examined cytologically by the millipore technique with Papanicolaou staining. The results were processed automatically. An approximately 25-fold increase in CSF cells (P<0·001), mainly meningeal, reticulohistiocytic, and monocytic types, was found to occur. The cortical gas filling rate had a positive correlation (P<0·001) with the increase of number of CSF cells. There were no significant differences between the cellular changes in different cerebral disorders. Thus, though the irritant effect of GEG gives a rich cell yield, diagnostic atypical cells in developmental disorders of the central nervous system probably rarely exfoliate into the lumbar CSF.